Mechanism and intervention measures of iron side effects on the intestine. Issue 12 (3rd July 2020) - Qi, Xiao; Zhang, Yuanxiao; Guo, Hang; Hai, Yu; Luo, Yane; Yue, Tianli
Abstract: Excess oral iron in the intestinal tract usually produces reactive oxygen species via Fenton and Haber-Weiss reaction, so oxidative stress is triggered. Lipid peroxidation procedurally appears, ferroptosis, apoptosis and necrosis are often induced, subsequently, mitochondrial damage, endoplasmic reticulum dysfunction and even cell death occur. As a result, the intestinal epithelial cells are destroyed, leading to the incompleteness of intestinal mechanical barrier. Simultaneously, iron supplement can change the compositions and metabolic processes of intestinal microbes, and the intestinal inflammatory may be worsened. In principle, the easier dissociation of Fe 2+ from oral iron supplements is, the more serious intestinal inflammation will occur. Fortunately, some interventions have been developed to alleviate these side effects. For instance, some antioxidants e.g. VE and ferulic acid have been used to prevent the formation of free radicals or to neutralize the formed free radicals. Furthermore, some new iron supplements with the ability of slow-releasing Fe 2+, e.g. ferrous citrate liposome and EDTA iron sodium, have been successfully prepared. In order to recover the intestinal micro-ecological balance, probiotics and prebiotics, bacterial consortium transplantation, and fecal microbiota transplantation have been developed. This study is meaningful for us to develop safer oral iron supplements and to maintain intestinal micro-ecological health.